Cellular variant of extraskeletal myxoid chondrosarcoma with Ewing’s sarcoma-like areas: a diagnostic pitfall in core needle biopsy - El Demellawy, Dina; Denardi, Franco; Alowami, Salem (Polish Journal of Pathology, 2010)
Extraskeletal myxoid chondrosarcoma (EMC) is a rare mesenchymal soft tissue tumour that poses diagnostic difficulty as it lacks a characteristic immunophenotype, in addition to its wide morphological spectrum. Microscopically, EMC shows strands and cords of relatively small cells with acidophilic cytoplasm that are occasionally vacuolated. Small cells with scant cytoplasm may comprise some EMC. We describe a rare and challenging case of EMC, which shows an unusual morphology with small blue cells, raising the possibility of PNET/Ewing’s sarcoma. The small cellular variant of EMC usually poses diagnostic difficulty, particularly during its evaluation in a core needle biopsy. Consideration of EMC, small cell variant, in evaluation of a blue cell tumour, may avoid a potential diagnostic pitfall. Proper diagnosis of EMC and its differentiation from PNET/Ewing’s sarcoma is crucial due to a difference in management protocols and prognostic outcome.